Awdarma teoriyasınıń rawajlanıw basqıshları hám lingvistikalıq ádis (SCIENCE and SOCIETY, 2025)
This article provides information on the historical stages of translation theory and the theoretical founda- tions of its development. The tasks of linguistic, cultural, and communicative relations, which are widely used in the activi- ties of translation theory, are also described. It is emphasized that linguocultural features, cultural interpretation, cultural vision, and creative abilities are the most important abilities that should be present in the translator’s activity.